Konsep Manusia Sempurna - Siti Saudah; Nusyirwan Nusyirwan (Jurnal Filsafat "WISDOM", 2004)
Human being is the highest creature among all creatures. Even, he is higher than the world and it is very important for it. The perfection of the world depends on him. Human being in relation to the universe is like spirit for body.The world without human being is like a unclear mirror which can not refract a picture. The picture of God can not be seen in the mirror cleary so God command that the clear mirror of the world can refract His picture clearly. The human being is the clearness of mirror and the shape of the picture.The most perfect mirror for God is the perfect human being because he refracts all the names and the behaviour of God However, other refract only a few parts of the parts of the names and the behaviour of God.The perfect human being, faces all existances of individualism. Spiritually he faces higher individualism; the body he faces lower individualism. His heart faces to (al-Arsh). His soul faces to apen (Al-Qalam) and his spirit faces (luah-Mahfudz)